Impacts of mowing and bud destruction on Centaurea solstitialis growth, flowering, root dynamics and soil moisture. (21st November 2013) - Spencer, D F; Enloe, S F; Pitcairn, M J; Ditomaso, J M; Zwerger, Peter
Summary Centaurea solstitialis (yellow starthistle) has invaded rangelands and natural areas in the western USA. There is evidence that mowing is a more effective method of reducing growth and seed production, compared with the well‐established and distributed bioagents. To test this hypothesis we measured C. solstitialis's growth and reproduction following two treatments (late spring and early summer bud/capitula destruction and shoot mowing) and measured C. solstitialis's growth and reproduction. We measured changes in soil moisture content to test the hypothesis that these manipulations differentially affect water usage by the invasive plant. Mowing produced shorter plants that weighed less. Bud damaged plants were not statistically different from untreated controls. The number of developed capitula was reduced 67% by mowing but was unaffected by bud damage. Mowed plants redistributed resources from root to flower production. Both treatments reduced mean capitulum diameter. This resulted in reductions of 76% and 21% in estimated seed number for mowed and bud damaged plants respectively. Root abundance decreased and root life‐span was reduced by both treatments. Soil moisture depletion was greatest from mid‐May to mid‐July (from 21% to 9%) and occurred after maximum root abundance. Mowing resulted in a delay in soil moisture depletion compared with the bud damaged plants or the untreated controls. Bud/capitula damage did not affect C. solstitialis's requirement for soil water. Overall, this study supported the hypothesis that mowing reduced C. solstitialis growth and reproduction more than bud damage alone. This information will aid managers in selecting a strategy for managing C. solstitialis in a particular habitat.